ДНК как модулятор протонной проницаемости на внутренней мембране митохондрий Solanum tuberosum, действующий на уровне переносчика адениннуклеотидов - Кулинченко, М.В.; Клименко, Е.С.; Вебер-Лотфи, Ф.; Диетриш, А.; Константинов, Ю.М. (Фактори експериментальної еволюції організмів, 2014)
Aims. To study the potential metabolic consequences of DNA import into mitochondria we investigated the effect of 200 bp length DNA on the permeability of inner membrane of tuber mitochondria in Solanum tuberosum in comparison with such an effect of adenine nucleotides (ADP, ATP), palmitic acid, palmitoyl-CoA and highly specific inhibitors of adenine nucleotide translocator as atractyloside and carboxyatractyloside. Methods. Freshly-isolated highly purified mitochondria from potato tuber (Solanum tuberosum) were used in all experiments. To evaluate the permeability of the inner mitochondrial membrane to H+-ions the swelling of mitochondria in the medium containing 100 mM NH4NO3, 20 mM tris-HCl (pH 7.4) was measured using LKB Ultrospec II UV-Visible spectrophotometer. Results. We showed that DNA in concentration 1 мМ is able to induce swelling of potato tuber mitochondria like such highly specific ligands of adenine nucleotide translocator as carboxyatractyloside and atractyloside. Therefore the increase in permeability of inner mitochondrial membrane to H+-ions is presumably explained by binding of DNA to active sites of ADP/ATP carrier. The stimulation of mitochondrial swelling by addition of DNA was removed by the addition of ADP in physiological concentrations. As for carboxyatractyloside and atractyloside, both these ligands increase DNA effect on mitochondrial swelling. Conclusions. We conclude that DNA is able to bind to specific binding sites of adenine nucleotide translocator in plant mitochondria and through conformational changes of this key membrane carrier to induce the increase of inner mitochondrial membrane permeability to H+-ions. We hypothesize that in some critical states of plant cell (bacterial and viral infections leading to increase of DNA concentration in cytoplasm) the DNA effect on ion membrane permeability observed in this study may serve as one from a set of signals inducing apoptosis.

Key words: mitochondria, Solanum tuberosum, DNA, mitochondrial swelling, adenine nucleotide translocator, inner membrane permeability to H+-ions.